Mettre la ville en atlas, des productions humanistes aux humanités digitales (Ausonius Éditions, 2022)
The French Society of Urban History, convinced of the relevance of the geohistoric approach to question the urban fact, dedicated its 2020 annual congress, in Bordeaux, to the status and roles of the city in atlas productions. This work represents the publication of eight of the congress contributions. In its standard meaning, the atlas is a compilation that combines in a universal perspective, cartographic productions and textual commentaries. It is over the long term, from humanist productions to digital humanities and according to all meanings of the term that the authors questioned, through the prism of the city, the ambitions and practices of this singular mode of representation. Why and how to transplant the city into an atlas? How efficient is the tool in the geohistorical approach to the city? The collected contributions analyze atlases from a dual perspective: the first considers the atlas as a tool for reasoning about the city, used since the Renaissance and mainly motivated by political and military logic ; the second, based on contemporary experiences, observes the urban historian as a producer of atlases.